TI_GERICHTE 12.2008.232 vom 18. Mai 2010 , Regresso per mutuo solidale (Gesamtschuldnerausgleich del diritto tedesco) - TI Tribunale d'appello (2010)
Regresso per mutuo solidale (Gesamtschuldnerausgleich del diritto tedesco)